The sources and quality of Iranian honey. Issue 4 (April 2021) - Khansaritoreh, Elmira; Salmaki, Yasaman; Akbari Azirani, Tayebeh; Henareh, Farnood; Alizadeh, Kamaleddin; Ramezani, Elias; Zarre, Shahin; Beckh, Gudrun; Behling, Hermann
Abstract: Iran is one of the largest honey-producing countries worldwide and is considered as an important source of honey for international markets. However, since Iran is not registered for honey export to Europe, the quality of Iranian honey remains unknown to European traders. As the first step in filling this gap, we analyzed 225 honey samples using palynology, sensory, nuclear magnetic resonance (NMR) and conventional physicochemical analyses as outlined by the European Union coordinated control plan. The results show that while various types of genuine unifloral honey can be harvested in Iran, 85% of collected samples were adulterated. Performing principal component analysis on physicochemical parameters reveals that feeding tablet sugar and syrup of C4 origin to bees during the foraging season is a common mode of fraud. Replacement of natural nectar with sugar syrup together with presence of intensive aftertaste from Taraxacum and Eryngium affect the taste of unifloral honeys produced in Iran. Abstract : Honey, adulteration, NMR, melissopalynology, sensory, physicochemical analyses